Attractiveness' Factor in Food Based Logo Design - Teddy Marius Soikun (Penerbit UMS, 2022)
This research aims to understand the factors of 'attractiveness" food-based in logo design. Based on an in-depth literature review, the research includes one design dimension, 'attractiveness.' "Attractiveness" is investigated on its influences on emotive consumer response. To reach the understanding of 'attractiveness,' one of the methods used is the Viewer's Impression Words (V.I.W.), a modification of Kansei Words (K.W.) usually found in Kansei Engineering.This method combines formalistic and visual semiotic analysis theory to achieve the Viewer's Impression Words (V.I.W.). Emotion Engineering presents a combination of quantitative and qualitative methodologies and is used to achieve loose principles to help designers understand the factors of an 'attractive' logo. This method is suggested as a new technique to improve the process of Emotion Engineering through understanding the factors of attractiveness in logo design and thus offer loose principles to help in 'problem-solving usually found in graphic design. 50 logos was selected as a design stimuli. These logos were then classified according to their domain which is food companies. Results showed that attractiveness is an important part of a food-based logo design from the suggested method. From the V.I.W, selected words suggested by participants (consumer), it can be transformed into loose principles to help new designers to design based on consumers' preferences. The findings also suggest that it may help designers reach 'attractiveness' in their logo by getting the idea of what is preferred in food logo design.